Menuju Multitude: Gerakan Mahasiswa “Bali Tidak Diam” Diantara Pengorganisasian dan Diversitas - Raharja, Umar Abdurrahman; -, Bandiyah; Pramana, Gede Indra (Jurnal Nawala Politika, 2021)
The research seeks to find Multitude indicators in the student movement "Bali Tidak Diam". This research uses the Multitude theory of Michael Hardt and Antonio Negri. The results of this study are first, in the singularity indicator the writer gets the results, namely the existence of various elements of society and students from various groups who participate in the "Bali Tidak Diam" movement. Second, in the indicators of democracy, the writer gets results, namely the existence of space for expression, equality, the opportunity given to each group from various elements to provide opinions or input in the movement. Third, in the organizational indicators the writer gets the result, namely the independent efforts made by students and the community to enlarge the "Bali Tidak Diam" movement. This research has answered about the creation of a movement that leads to multitude in the "Bali Tidak Diam" movement. Keywords: student movement, multitude, singularity, democracy